1989
DOI: 10.1111/j.1471-4159.1989.tb01881.x
|View full text |Cite
|
Sign up to set email alerts
|

A Glycine Site Associated with N‐Methyl‐d‐Aspartic Acid Receptors: Characterization and Identification of a New Class of Antagonists

Abstract: Membranes from rat telencephalon contain a single class of strychnine-insensitive glycine sites. That these sites are associated with N-methyl-D-aspartic acid (NMDA) receptors is indicated by the observations that [3H]glycine binding is selectively modulated by NMDA receptor ligands and, conversely, that several amino acids interacting with the glycine sites increase [3H]N-[1-(2-thienyl)cyclohexyl]piperidine ([3H]TCP) binding to the phencyclidine site of the NMDA receptor. The endogenous compound kynurenate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
323
1
4

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 714 publications
(340 citation statements)
references
References 23 publications
12
323
1
4
Order By: Relevance
“…The most parsimonious interpretation of these data is that KYNA-mediated blockade of the glycine B site (IC 50 : 10-15 mM; Birch et al, 1988a, b;Kessler et al, 1989;Danysz et al, 1989) is responsible for the observed deficit in auditory gating. This notion would be consistent with the fact that KYNA levels comparable to those attained in the present study are capable of blocking the convulsant and excitotoxic effects of NMDA receptor agonists (Vécsei et al, 1992;Santamaria et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The most parsimonious interpretation of these data is that KYNA-mediated blockade of the glycine B site (IC 50 : 10-15 mM; Birch et al, 1988a, b;Kessler et al, 1989;Danysz et al, 1989) is responsible for the observed deficit in auditory gating. This notion would be consistent with the fact that KYNA levels comparable to those attained in the present study are capable of blocking the convulsant and excitotoxic effects of NMDA receptor agonists (Vécsei et al, 1992;Santamaria et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…KYNA is a noncompetitive antagonist of the NMDA receptor ion-channel complex, acting on the strychnine-insensitive glycine recognition site (Birch et al, 1988), with an IC 50 in the low micromolar range (IC 50 ¼ 7.9 mM; Ganong and Cotman, 1986;Kessler et al, 1989;Parsons et al, 1997). Furthermore, a recent study showed that KYNA blocks the a7* nicotinic receptor with the same IC 50 value as for the glycine-site of the NMDA receptors (Hilmas et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, intracerebral application of large amounts of KYNA has long been known to exert neuroprotective and anticonvulsant effects in experimental animals (Foster et al, 1984). At much lower concentrations, KYNA inhibits the strychnine-insensitive glycine coagonist site of the NMDA receptor (IC 50 : 8mM; Kessler et al, 1989), and recent evidence favors a physiological action of KYNA as an Animals were killed 1 h after the final injection of nicotine (1 mg/kg, s.c., b.i.d. ), and the blood was processed as described in the text.…”
Section: Discussionmentioning
confidence: 99%
“…KYNA, long known as an antagonist of the glycine coagonist site of the NMDA receptor (Kessler et al, 1989), blocks a7 nAChR activity at even lower, endogenous brain concentrations (Hilmas et al, 2001), and reductions in brain KYNA levels were recently found to increase a7 nAChR function (Alkondon et al, 2004). It is therefore conceivable that nicotine-induced fluctuations in brain KYNA levels influence the activity of a7 nAChRs (Hilmas et al, 2001).…”
Section: Introductionmentioning
confidence: 99%